(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study appraised employee recruitment practices utilized by managers of small and medium scale enterprises (SMSEs) for improved performance in Delta State. One research question guided the study and two hypotheses were tested. Descriptive survey design was adopted for the study. The study was carried out in Delta State of Nigeria. The decision to use Delta State for the study is informed by the fact that the state has many SMSEs which are experiencing reduction in business size, slow expansion rate and even business failure. Population for the study consisted of 420 managers of SMSEs in the general business service sector operating in Delta State. The entire population was used in the study without sampling. A structured questionnaire comprising seven items which was validated by three experts in the field was used to collect data. Mean and standard deviation were used to answer the research question and determine the closeness of the respondents’ mean while Analysis of Variance (ANOVA) and t-test were used in testing the null hypotheses at 0.05 level of significance. Findings revealed that managers of SMEs in Delta State utilize employee recruitment practices to a moderate extent. It was also revealed that years of business experience and gender of the respondents did not significantly influence their mean ratings. Based on these findings, it was recommended among others, that managers of SMSEs should make concerted efforts to improve their employee recruitment process and systems through purchase and reading of books and journals on employee recruitment practices. It was also recommended that the National Association for Small and Medium Scale Entrepreneurs (NASME) should organize conferences and workshops for her members in order to educate them on the importance of recruiting the right employees in their organization.